1994
DOI: 10.1002/app.1994.070511307
|View full text |Cite
|
Sign up to set email alerts
|

Chemical crosslink densit and network structure of natural rubber vulcanizates modified with phosphorylated cardnol prepolymer

Abstract: The chemical crosslink density (CLD) and network structure of natural rubber ( N R ) vulcanizates, modified with phosphorylated cardanol prepolymer (PCP) , have been studied by equilibrium swelling and other chemical methods. The PCP-modified NR vulcanizates showed lower CLD, as compared to the unmodified NR samples, the decrease being lesser for the semiefficient vulcanization (SEV) system, as compared to the conventional (CV) and efficient (EV) vulcanization systems. The superior tensile characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 10 publications
4
50
0
Order By: Relevance
“…This has been ascribed to the residual acidity of PCNSL and the probable complex formation of Cure Characteristics Zn 2/ ions of the cure activator (ZnO) with the phosphate groups of PCNSL. 9 The effect of PCNSL dosage on the cure character-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been ascribed to the residual acidity of PCNSL and the probable complex formation of Cure Characteristics Zn 2/ ions of the cure activator (ZnO) with the phosphate groups of PCNSL. 9 The effect of PCNSL dosage on the cure character-…”
Section: Resultsmentioning
confidence: 99%
“…9 It is possithe HAF-black-filled vulcanizate decreased at a higher rate compared to that containing silica ble that these mechanisms may also operate in the filled samples. Besides, the plasticizing effect and china clay with the increase in concentration of PCNSL.…”
Section: Mechanical Properties Of the Vulcanizatesmentioning
confidence: 97%
“…The phosphorus-modified CNSL prepolymer has been found to act as a multifunctional additive in NR in various roles. It can act as cross-linkable plasticizer, softener, tackifier, antidegradant and improver of thermal stability, improver of mechanical properties of vulcanizates, such astensile strength, tear strength and fatigue resistance, and coupling agent between filler and rubber [166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182]. Introducing free radical polymerizable moieties would enable cardanol to become a potential monomer for the molecular design of high-value polymers [183][184][185].…”
Section: 'Synthetically-inspired' Materials From Natural Monomersmentioning
confidence: 99%
“…Previous studies have shown that PCNSL/PCP 12 could function as a multifunctional additive in NR and synthetic rubbers in various roles as a crosslinkable plasticizer, a softener, a tackifier, an antidegradant, an improver of the thermal stability and mechanical properties of vulcanizates (tensile strength, tear strength, and fatigue resistance), and a coupling agent between silica filler and NR, leading to improvement in resistance to crack propagation. [12][13][14][15][16][17][18][19][20] It has been reported previously that carbon-blackfilled EPDM vulcanizates containing PCNSL showed improvements in cure rate, tear strength, thermal stability, and resistance to thermo-oxidative decomposi-tion as compared to a commercial plasticizer. 18 A recent study on the melt rheology of EPDM modified with 5-10 phr of PCNSL on a capillary rheometer over a wide range of temperatures and shear rates showed the plasticizing effect of the additive on the rubber and the consequent improvement in melt processability.…”
Section: Introductionmentioning
confidence: 99%